Farmer Groups and Agricultural Development in Nyakabande Sub-County Kisoro District. - Munyana, Mercy (Kabale University, 2025)
The study examined farmer groups and agricultural development in Nyakabande sub-county Kisoro district. The study was based on three objectives to assess the current agricultural practices in Nyakabande sub-country, Kisoro district, to identify the challenges faced by farmers groups in Nyakabande sub-country, Kisoro district, to explore the opportunities for farmer groups and agricultural development in Nyakabande sub country, Kisoro district. The study used a descriptive research design that aimed at generating information after the incident had occurred; the Qualitative approach included the use of interviews. Data was collected using a questionnaire and interview guide, and simple random and purposive sampling methods were used. Both qualitative and quantitative methodologies were used to analyze data as a sample size of 59 respondents was used. The study revealed current agricultural practices in the Nyakabande sub country, Kisoro district and these included agroforestry practices, shifting cultivation, intensive farming, commercial agriculture, mixed crops, and livestock. The study revealed the opportunities for farmer groups and agricultural development in Nyakabande sub-country, Kisoro district and these included joining associations help farmers to get capital, increased need for coordination in agriculture production, extension and education services, improvement in agriculture production, the effective operation can create farmers group opportunities to get production market, Strengthen farmers market. Lastly, the study revealed the opportunities for farmer groups and agricultural development in Nyakabande sub-country, Kisoro district and these included strengthening the farmers' market, increased need for coordination in agriculture production, extension, and education services, improvement in agriculture production, an effective operation can create farmers group opportunities to get production market, joining associations help farmers to get capital. The study recommended that the facilitators of the farmers' groups must target and educate younger household heads within the region to ensure maximum participation and sustainability of the group.